Research on the Impact of Family Capital on Individual Employment Quality—Empirical Analysis Based on CFPS Data - Huang, Yingjie; He, Peiyi (International Journal of Global Economics and Management, 2024)
Based on the data of China Family Panel Studies (CFPS) in 2020, this paper uses OLS and Logit regression models to explore the impact and mechanism of family capital and education acquisition on individual employment quality. The study found that family capital has a significant positive impact on the quality of personal employment; the effect of family capital on the improvement of objective employment quality is greater than that of subjective employment quality. Family capital can have a positive impact on the quality of individual employment through education acquisition, and education acquisition shows a significant mediating effect. Through heterogeneity analysis, it is found that the employment quality of eastern provinces in China is significantly higher than that of central and western provinces. There are significant differences in the quality of employment between urban and rural individuals. Individuals in rural low-education and low-income families have significant disadvantages in the quality of employment compared with urban high-education and high-income families. The promotion effect of family capital on the employment quality of middle-educated workers is significantly higher than that of low-educated groups, and the phenomenon of " degree inversion " in the employment of high-educated people is more prominent. Therefore, China should improve the relevant employment quality assurance system, strengthen employment guidance, increase investment in education funds in economically lagging areas, and improve education to promote high-quality employment.